Outros Zadigs e novos destinos: histórias e memórias na construção de uma residência multi [e inter] profissional para o SUS - Schiavo, Taismane Clarice Coimbra Ricci Vieira (2023)
This dissertation is about memories of a social worker from Espírito Santo. The author uses the process of a trip as an analogy, associating the research elements with items such as maps, itineraries, luggage and photographs. She had multiple encounters and interactions during her Multiprofessional Residency with the Brazilian Unified Health System (SUS). She researched the local challenges in management and care for people in severe psychological distress. The author was encouraged by the recently created school of public health in the State of Espírito Santo - ICEPi - Instituto Capixaba de Ensino, Pesquisa e Inovação em Saúde, to broaden her professional knowledge by furthering her professional experience in another academic setting as well. She pursued the Professional Master Degree in Clinical Management at The Federal University of São Carlos (UFSCar-SP). In a clear, deep, engaging and provocative way, the researcher sought to understand and analyze the perception of resident professionals who attended ICEPi's Multiprofessional Residency Program in Mental Health (PRM-SM) between March 2021 and February 2023. Its focus was the development of attributes for the competence of collaborative interprofessional practice in the SUS. In a diverse and innovative linguistic proposal, the author organized a qualitative, descriptive, and exploratory research, broadly intersected by narrative resources. She used a narrative method for her data collection instrument, and presented her writing according to scientific standards. Based on a brief survey, the study entailed the forming of critical, reflective narratives which were created individually by the residents participating in the research. It was followed by integrating these discourses into a single synthesized narrative which was validated by the collection itself. Based on this data and anchored on theoretical references of Health Care, Multiprofessional Residencies in the SUS and Interprofessional Education, the author identified three thematic axes: Education-Teaching, Work-Service, and Care-Community. She merged the data in three areas of perceptions: representations, learning, and contributions. Guided by hermeneutic-dialectic analysis, the researcher revealed potentialities and gaps in training. She pointed out that the PRM-SM has contributed to the development of a collaborative interprofessional practice in the SUS, and the need for complementary scientific research should be carried out in order to affirm the real effectiveness of the Program for Interprofessional Education for the SUS. The findings of this research also identify that interprofessionality would be enhanced through education and training because it sustains, reinforces, and consolidates the work and care processes expected through the SUS. In a poetic and philosophical closing, the author uses the short story by Zadig, “Destiny”, written by the French enlightener Voltaire. By demarcating its implications in work and life, the researcher calls us to a final reflection: it is urgent to rescue the essence of our human identity, whose realization is both unique to the individual and integrated with his/her community.